Hidrolisis Xilan Bagas Menggunakan Xilanase Bacillus subtilis XJ28 dan Karakterisasi Enzimnya - A, Gading Wilda; ., Yopi; Meryandini, Anja (Perhimpunan Biologi Indonesia, 2015)
Xylanase extracellular enzyme is produced by various microbes. Hydrolysis of bagasse xylan can produced xylooligosaccharide. The main components of hemicellulose was xylan at bagasse. IdentificationBacillus subtilisXJ28 using primer 16S RNA. The qualitative test used Congo-Red stainning, whereas quantitative test used Dinitrosalicyclic Acid (DNS) methode. The hydrolyzing product was analysed used TLC (Thin Layer Chromatography). This research aims were to characterized xylanase from isolate XJ28 and analyzing the hidrolyzing product from xylan bagasse. Pretreatment process included delignification using sodium hypochlorite 1% and xylans extraction using alkaline (NaOH 15%) as the solvent. The result of the xylans extracted from bagasse was 9,9% xylan and after purification was obtained 3,4% soluble xylan. Xylanase activity has the highest activity at 96 h of incubation time with activity 11,3 U/mL. Xylanase Bacillus subtilis XJ28has the optimum condition at pH 7 and 50 ÃÂºC and stable up to 72 hr ofÃÂ incubation time at room temperature and 4 ÃÂºC. The hydrolysis product using xylanase crude enzyme was reducing sugar with molecular weight aroundÃÂ of sucrose and oligosaccharide.ÃÂ Keywords: xylanase, xylan bagasse, hydrolysis, TLC.ÃÂ